Perceived Motor Competence Mediates the Relationship Between Gross Motor Skills and Physical Activity in Youth With Visual Impairments. Issue 2 (3rd April 2022) - Brian, Ali; Starrett, Angela; Haibach-Beach, Pamela; De Meester, An; Taunton Miedema, Sally; Pennell, Adam; Lieberman, Lauren J.
ABSTRACT: Children with visual impairments typically demonstrate lower levels of motor competence, physical activity, and perceived motor competence compared to their peers without visual impairments. Stodden and colleagues purport that perceived motor competence mediates the relationship between motor competence and physical activity for youth without visual impairments. Purpose: The purpose of this study was to test whether perceived motor competence mediates the relationship between motor competence and physical activity for youth with visual impairments. Methods: Participants ( N = 138; boys = 81, girls = 57) were age 9–18 years ( Mage = 13.37, SD = 2.34) with visual impairments. Participants completed the Test of Gross Motor Development-3, the Test of Perceived Physical Competence-VI, and the Physical Activity Questionnaire. Results: Locomotor skills predicted perceived motor competence, which predicted physical activity. Perceived motor competence showed a mediation effect on the path from locomotor skills to physical activity. There was no significant relationship between locomotor skills and physical activity. Conclusion: The results from this study provide initial evidence to support the hypothesis proposed by Stodden and colleagues. These data provide a rationale to include both perceived and actual motor competence within targeted intervention strategies to increase physical activity behaviors for youth with visual impairments. Future research should consider following participants longitudinally to test the roles of perceived and actual motor competence as factors supporting positive developmental trajectories for health.